Pengaruh Pemahaman Nasabah Pada Jenis Produk Terhadap Kelancaran Pembayaran Angsuran Di BMT Niaga Utama Purwakarta - Syanti Herlinawati; Asep Dede Kurnia; Jalaludin Jalaludin (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2021)
The banking industry is currently experiencing rapid development where the main activity of financial institutions is to collect funds and channel them back to the public in the form of credit/financing. Problems that arise from the financing process are bad funds from customers as an unavoidable risk with several indicators of causes such as customer income, disasters experienced by customers, awareness and refunds from understanding the financing contract contract. This study aims to analyze the effect of customer understanding on mudharabah products, murabahah products, and murabahah products and to examine the effect of average customer understanding on payment growth at BMT Niaga Utama Purwakarta. This research was conducted by quantitative descriptive method using a sample of 34 customers from a population of 67 customers. Determination of the research sample is through a random sampling system with a Likert scale. The results of this study indicate that the customer's understanding of the mudharabah product is stated to be significant for payment payments with a value of rcount (0.84) > rtable (0.648), while the customer's understanding of the musyarakah product is stated to have no significant effect on payment performance with a value of rcount (0.697) < rtable (0.738). As for the influence of customer understanding of the value of murabahah products, the sig. (2-tailed) number is 0.000 which is smaller than the level of significant (α) 5% and is declared significant. While the effect of the known average value of Ucount = 22 > Utable 17 shows that there is no difference between understanding the product of mudharabah, musyarakah and murabahah on installment payments.